Analysis of Problem Based Learning Implementation for Enhancing Vocational High School Students Critical Thinking Skills - Mohammad Wildan Habibi; Intan Dwi Febrianti; Varsaretha Najmi Rohadatulaisyi; Pinggan Marinda Yuwana; Alifia Deandita Amir; Wahid Arya Fikriyansyah Wardhana (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2026)
Students’ critical thinking skills remain relatively low because the learning process tends to be teacher-centered. This situation highlights the need to implement a learning model that can enhance students’ active participation during learning activities. This study aims to examine the effectiveness of implementing Problem Based Learning (PBL) in improving students’ critical thinking skills through a Systematic Literature Review (SLR). The study was conducted in accordance with the PRISMA 2020 guidelines, which include the stages of identification, screening, eligibility, and included studies. Articles were searched in the Google Scholar, Scopus, and DOAJ databases, covering publications from 2023 to 2025. A total of 30 articles were selected based on inclusion and exclusion criteria and then analyzed using narrative synthesis. The results indicate that the implementation of PBL generally has a positive impact on enhancing students’ critical thinking skills, as evidenced by improved learning outcomes, student engagement in the learning process, problem-solving abilities, and peer collaboration. The novelty of this study lies in the integration of the latest research findings regarding the effectiveness of PBL for vocational high school students based on publications from 2023 to 2025. However, the implementation of PBL still faces several obstacles, such as limited learning time and teachers’ readiness to implement Problem Based Learning.